2016
DOI: 10.1186/s12870-016-0942-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis reveals novel host molecular mechanisms associated with thermotherapy of ‘Ca. Liberibacter asiaticus’-infected citrus plants

Abstract: BackgroundCitrus Huanglongbing (HLB), which is linked to the bacterial pathogen ‘Ca. Liberibacter asiaticus’ (Las), is the most devastating disease of citrus plants, and longer-term control measures via breeding or genetic engineering have been unwieldy because all cultivated citrus species are susceptible to the disease. However, the degree of susceptibility varies among citrus species, which has prompted efforts to identify potential Las resistance/tolerance-related genes in citrus plants for application in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 76 publications
2
17
0
Order By: Relevance
“…Additional support for this can be found in a proteomics analysis where total protein extracts from heat-treated, Las-positive, Citrus paradisi trees were compared to healthy trees that had not undergone heat-treatment. 39 Because several of the same genes were found to be upregulated in the heat-treated trees in both the current study ( Supplementary Table 1 ) and the proteomics study by Nwugo et al , especially those chaperones associated with heat shock, it can be concluded that a common response exists. In addition, consistent patterns of regulation were found in spite of the fact that the present study was performed on Valencia sweet orange trees and the proteomics analysis was performed on Duncan grapefruit, hence, strengthening the hypothesis that common stress pathways are induced in Las-infected citrus plants through heat regardless of citrus species.…”
Section: Discussionsupporting
confidence: 53%
“…Additional support for this can be found in a proteomics analysis where total protein extracts from heat-treated, Las-positive, Citrus paradisi trees were compared to healthy trees that had not undergone heat-treatment. 39 Because several of the same genes were found to be upregulated in the heat-treated trees in both the current study ( Supplementary Table 1 ) and the proteomics study by Nwugo et al , especially those chaperones associated with heat shock, it can be concluded that a common response exists. In addition, consistent patterns of regulation were found in spite of the fact that the present study was performed on Valencia sweet orange trees and the proteomics analysis was performed on Duncan grapefruit, hence, strengthening the hypothesis that common stress pathways are induced in Las-infected citrus plants through heat regardless of citrus species.…”
Section: Discussionsupporting
confidence: 53%
“…ROS regulating enzymes are upregulated at the protein level in grapefruit after CLas infection (93,98). Citrus undergoing thermotherapy to treat HLB exhibited increased peroxidase accumulation (99). Additionally, bioinformatic analyses comparing four RNA-seq studies on HLB illustrated that tolerance is linked with the induction of redox-related genes involved in both young and mature leaf tissues (100).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies generally focused on the differentially expressed genes or proteins (DEPs) mediated by CLas in leaves, fruits and roots [26,[28][29][30][31][32]. Leaves infected with CLas display yellowing and blotchy mottled appearances.…”
Section: Introductionmentioning
confidence: 99%